Measurement of morphing wing deflection by a cross-coherence fiber optic interferometric technique. (7th December 2017) - Tomić, Miloš C; Djinović, Zoran V; Scheerer, Michael; Petricevic, Slobodan J
Abstract: A fiber-optic interferometric technique aimed at measuring the deflection of aircrafts' morphing wings is presented. The wing deflection induces a strain in the sensing fiber optic coils that are firmly fixed onto the wing. A change of the phase angle of the light propagating through the fiber is measured by an 'all-in-fiber' Michelson interferometer based on a 3 × 3 fiber-optic coupler. Two light sources of different coherence lengths and wavelengths are simultaneously used to ensure a wide measurement range and high accuracy. A new technique for determination of the zero deflection point using the cross-correlation of the two interferograms is proposed. The experiments performed on a specimen made of a carbon-fiber-reinforced plastic honeycomb structure demonstrated a relative uncertainty <1% and a precision of about 0.06° in the measuring range ±5° of the morphing wing deflection.